Phyto-intruders in oral tissues: A polarized light microscopic study - Divya, Bose; Vasanthi, V.; Ramadoss, Ramya; Kumar, A. Ramesh; Krishnan, Rajkumar; Raja, K. K. (International Journal of Health Sciences, 2021)
Objectives: Foreign body reactions are common in the oral cavity due to its proximity to the external environment. Rarely, foreign body of plant origin may be encountered in the histopathological sections making the diagnosis problematic. The aim of the present study was to analyze the histological features of various products of plant origin emphasizing on the pathogenesis of tissue reaction occurring in response to their implantation. Methods: This observational study included various plant products or phytoproducts commonly consumed in South Indian diet such as rice, curry leaves, coriander leaves, spinach leaves, coconut, green chilli, onion, French beans, urad dal, lentil beans, mustard seed, ginger, and garlic. Formalin-fixed specimens were routinely processed and stained with hematoxylin and eosin. The slides were viewed under light microscope and polarized microscope and evaluated by two oral pathologists. Results: Each of the phytoproducts had distinctive histological appearance and exhibited positive birefringence. Phytoproducts such as rice, curry leaves, French bean, onion, and green chilli resembled pathological structures such as calcifications, ghost cells, clear cells, atypical adipocytes, and fungal hyphae, respectively. Conclusions: Plant products appear as puzzling structures in histological section posing difficulties to the pathologist. Recognition of these structures as foreign body based on their histological appearance is inevitable and their identification may avoid unnecessary delay in treatment planning. The current study serves as an atlas for the histology of extraneous material study and also as a reference for the pathologists whenever mystifying structures are encountered.